The Effect of Leadership on the Successful Implementation of High-Performance Work Systems (HPWS) with Organizational Commitment and Innovation Culture as Intervening Variables at PT PLN (Persero) UP3 Mojokerto - Saputro, Tandi; Rosidi, Rosidi; Dahlan, Ahmad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The increasingly dynamic and competitive environment faced by state-owned enterprises highlights the importance of effective leadership in ensuring the successful implementation of strategic human resource management practices. This study examines the effect of Leadership on the successful implementation of High-Performance Work Systems (HPWS), with Organizational Commitment and Innovation Culture serving as intervening variables, at PT PLN (Persero) UP3 Mojokerto. Using a quantitative research design, data were collected through a census survey of all 85 permanent employees and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that leadership has a positive and significant direct effect on HPWS, as well as on organizational commitment and innovation culture. Furthermore, organizational commitment and innovation culture were found to have significant positive effects on HPWS and to partially mediate the relationship between leadership and HPWS. These findings indicate that leadership enhances HPWS implementation not only through direct managerial influence but also indirectly by strengthening employees’ psychological attachment to the organization and fostering an innovation-oriented work environment. Overall, this study provides empirical evidence that integrating leadership practices with efforts to build organizational commitment and innovation culture is essential for achieving sustainable HPWS, particularly within the context of Indonesian state-owned enterprises